2019
DOI: 10.3390/s19051141
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Internet of Things (IoT) Authentication Schemes

Abstract: The Internet of Things (IoT) is the ability to provide everyday devices with a way of identification and another way for communication with each other. The spectrum of IoT application domains is very large including smart homes, smart cities, wearables, e-health, etc. Consequently, tens and even hundreds of billions of devices will be connected. Such devices will have smart capabilities to collect, analyze and even make decisions without any human interaction. Security is a supreme requirement in such circumst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
186
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(189 citation statements)
references
References 152 publications
0
186
0
3
Order By: Relevance
“…The symbols CFY, UFY, A ARA, FSY, PVY, ROM, FVTA, √ , and ⨵ indicate confidentiality, unforgeability, authen integrity, anti-replay attack, forward secrecy, public verifiability, random oracle model verification through AVISPA, satisfying the service, and does not satisfy, respectively. The is clearly shown that, our proposed CB-SN meet all the claimed security services and the s i.e., Li et al [22], Omala et al [15], Gao et al [24], Braeken et al [17], Braeken et al [19] Sche and 3 do not meet the services such as FSY and PVY, as well as FVTA or some other verificat t + 1) 2 (2) Note, ℎ points are different from elliptic curve [26]. It forms the divisors which are the formal sum of finite integers like = ∑ i i, where i ℑ and i ℎ .…”
Section: Security Performancementioning
confidence: 93%
See 2 more Smart Citations
“…The symbols CFY, UFY, A ARA, FSY, PVY, ROM, FVTA, √ , and ⨵ indicate confidentiality, unforgeability, authen integrity, anti-replay attack, forward secrecy, public verifiability, random oracle model verification through AVISPA, satisfying the service, and does not satisfy, respectively. The is clearly shown that, our proposed CB-SN meet all the claimed security services and the s i.e., Li et al [22], Omala et al [15], Gao et al [24], Braeken et al [17], Braeken et al [19] Sche and 3 do not meet the services such as FSY and PVY, as well as FVTA or some other verificat t + 1) 2 (2) Note, ℎ points are different from elliptic curve [26]. It forms the divisors which are the formal sum of finite integers like = ∑ i i, where i ℑ and i ℎ .…”
Section: Security Performancementioning
confidence: 93%
“…Confidentiality means that the contents of a plain text (m) should hide from intruders and the intruders cannot get any meaning from the signcrypted text without knowing the shared secret key. In the proposed CB-SN scheme, if the intruders desire to scramble the contents of a plain text from a signcryption text = {C,A, S}, then it is mandatory for them to reveal the shared secret key SK by computing Equation (2). To compute this equation, it is important for the intruders to extract Ω from Equation (3), which is hard for them because this leads to computing ℎ − .…”
Section: Confidentialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Still, security is a big challenge in digital image watermarking. More recently, internet of things (IoT)-based authentication schemes have provided supreme security without human interaction [114], where more encryption can be done outside the image contents. Furthermore, blockchain-based authentication schemes also provide high levels of security.…”
Section: Challenges Of Image Watermarking Methodsmentioning
confidence: 99%
“…With the transport of messages from one device to the other authenticated and private, one must take care of the user authentication. There are a number of authentication schemes that can be used in IoT . Our work focuses on the post authentication part, in which the user is already cleared for access to the IoT system.…”
Section: Related Workmentioning
confidence: 99%